Jeux Sans Frontières: Tax Competition and Tax Coordination When Countries Differ in Size - Kanbur, Ravi; Keen, Michael (American Economic Review, 1993)
Closer international integration is putting increasing pressure on existing national tax structures. This paper uses a simple two-country model to address a range of consequent policy concerns, focusing particularly on the role of country size. Differences in size exacerbate the inefficiency from noncooperative behavior, harming both countries. The smaller country loses from harmonization to any tax rate between those set in the noncooperative equilibrium, but both countries gain from the imposition of a minimum tax anywhere in that range. The fully optimal response to freer cross-border trade, however, may be to do nothing.